(untitled) (JURNAL PROTEKSI KESEHATAN, 2023)
The family planning program is an effort to control birth rates and pregnancy spacing with contraception. The results of reports from the Gilingan Health Center on the availability of types of contraceptives in using hormonal contraception were 53% and non-hormonal contraception 47%. The Pandemic Period is a transitional condition and adjustment to new habits that must be adapted to government regulations. Descriptive survey research with a retrospective approach, population 1,199, sample 92 respondents, research instrument using a closed questionnaire, univariate data analysis. The results showed that the majority of respondents were aged 31-40 years as many as 51 respondents, the last education was SMA/SMK as many as 36 respondents and the majority of respondents worked as many as 50 respondents, with less knowledge as many as 37 respondents and the majority chose contraception using long-term contraception as many as 57 respondent. It is necessary to socialize and send a health promotion team to provide health education to hormonal and non-hormonal family planning acceptors to increase knowledge in choosing contraceptives used by family planning acceptors.